Web-Based E-Marketing Application for Balinese Art Studio - Hardinugraha, Wahyu; Sudana, Oka; Githa, Dwi Putra (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol. 9, No. 1, April 2021, 2021)
Balinese art and culture are unique because they may not be found in other regions. This uniqueness provides a characteristic and an attraction for foreign and domestic tourists visiting the island of Bali. The art studio is a place to provide traditional performing arts. The constraints experienced by art studios generally prevail in the manual marketing of art services, while the public or consumers experience problems ordering these performing arts services. E-Marketing is an online marketing medium with the help of the internet, which aims to expand the marketing of performing arts services without being limited by space and time. The method used in this study includes five main stages, namely, requirements analysis, system design, implementation, testing, and system maintenance. This research produces an E-Marketing Application for Sanggar Seni Bali with a website as the mediator. The Black Box test results show that all the system functionality components have been running successfully. The questionnaire analysis based on the answer scale percentage results shows that this application has been running well, responds according to the data needed, and is very suitable to be applied to people, especially those who need assistance in ordering traditional performing arts services. The implementation of this application will indirectly be a means of promoting traditional performing arts.